Ectoparasite insects of bats from the fields and weedlands eco-region of Argentina - Autino, Analia Gladys (2020)
New information is presented for bats and their ectoparasite insects from the Argentine Field and Weedlands Ecoregion. Bats of the families Molossidae, Phyllostomidae and Vespertilionidae containing ectoparasites belonging to families Polyctenidae (Hemiptera), Nycteribiidae and Streblidae (Diptera) were collected. Here is presented the first record of Hesperoctenes cartus Jordan, 1922 for Argentina. Basilia plaumanni Scott, 1940 and H. vicinus Jordan, 1922 are added to the province of Misiones and Paratrichobius longicrus (Miranda Ribeiro, 1907) is added to the province of Corrientes.Additionally, the distributions of some ectoparasite insects are extended and new host-ectoparasite associations are reported.